1997
DOI: 10.1080/096381897336854
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based techniques and the death of the beancounter

Abstract: In a study of eleven medium and large sized companies we found clear evidence that management accountants were seen by operational managers as 'beancounters'. This term has become common in the literature in recent years and we define a beancounter as, 'an accountant who produces financial information which is regarded as of little use in efficiently running the business and, as a result, its production has become an end in itself.' Furthermore many management accountants recognized this image. All of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 11 publications
3
99
0
8
Order By: Relevance
“…The mill controller had allowed 'outsiders' -both the production engineers and external consultants -to work on ABC models without management accountants actively taking part in them (cf. the third scenario by Friedman and Lyne, 1997). As a result of this the mill controller did not feel very familiar with ABC tools, and did not create information which others would have found useful in activity-based costing projects.…”
Section: Changing Cost Accounting Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mill controller had allowed 'outsiders' -both the production engineers and external consultants -to work on ABC models without management accountants actively taking part in them (cf. the third scenario by Friedman and Lyne, 1997). As a result of this the mill controller did not feel very familiar with ABC tools, and did not create information which others would have found useful in activity-based costing projects.…”
Section: Changing Cost Accounting Techniquesmentioning
confidence: 99%
“…On the basis of the earlier literature we examined John's role change from the following viewpoints that evinced as areas having a possible impact on management accounting role change: changing cost accounting techniques (Friedman and Lyne, 1997;2001), changing ICT systems (Granlund & Malmi, 2002;Scapens & Jazayeri, 2003;Caglio, 2003;Newman & Westrup, 2005), John's interest in business development that allowed him acquire expertise beyond the traditional bean counter job description (Granlund & Lukka, 1997, 1998aBurns & Baldvinsdottir, 2005;Vaivio 2006;Järvenpää 2007) and his ability for social networking in order to make allies and downgrade competitors in the organizational jungle (Ezzamel & Burns, 2005;Vaivio & Kokko, 2006).…”
Section: The Role Change Of Business Controllersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoffjan (2004) on the other hand is more specific in his claims that the negative perception is a consequence of accountants' obsessive focus on cost reduction. McHugh, Fahy and Butler (1998) and Friedman and Lyne (1997) found that the tension is reduced and the perceived image is more positive when there is a flatter organisational structure which generally results in increased interaction between accountants and their co-workers. This study found that most non-contact participants formed either abstract or very specific perceptions of accounting and accountants thus supporting Allport's claims that the application of the contact theory is complicated.…”
Section: Interview Responsesmentioning
confidence: 99%
“…The contact hypothesis has led Dodson and Price (1991), Fedoryshyn and Tyson (2003), Friedman and Lyne (1997), Larkin (1991) and Cory (1992) to recommend increased public exposure to, and contact with, accountants as a strategy for better informing people of the duties undertaken by accountants. Regrettably, however, the effectiveness of this strategy on people's perceptions of accounting and accountants has received little attention from researchers.…”
Section: Career Choice Factorsmentioning
confidence: 99%